If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6x + -3) + (9 + -7x) = 0 Reorder the terms: (-3 + 6x) + (9 + -7x) = 0 Remove parenthesis around (-3 + 6x) -3 + 6x + (9 + -7x) = 0 Remove parenthesis around (9 + -7x) -3 + 6x + 9 + -7x = 0 Reorder the terms: -3 + 9 + 6x + -7x = 0 Combine like terms: -3 + 9 = 6 6 + 6x + -7x = 0 Combine like terms: 6x + -7x = -1x 6 + -1x = 0 Solving 6 + -1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = 0 + -6 -1x = 0 + -6 Combine like terms: 0 + -6 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6
| 40-5(2x+10)=1 | | (3x-y)/(2x-y) | | 0.15t+2.50=6 | | 12.34+.08x=13.09-.11x | | -3+4k=5 | | 9m+32=6-4 | | 41+17.25x=24+21.50x | | -2x+3-5x-1=4x+5+x-1 | | 6(x+2)-(2x-3)= | | 3x^2+9xy+6y^2=0 | | 0=-16+t | | (4y-9)+40+5y=180 | | -y+7=15 | | 6(x-30)-5(x+35)=45-4(x-15) | | w-0.5=16 | | (x-3i)(x+3i)(x-(1+2i))(x-(1-2i))(x-6)=0 | | 15+47(922)= | | 9(-7+180)= | | 5(x+2)-4(x+1)=1 | | 0.7p+4.6=6.3-0.2p | | 5(-x+2)-4(x+1)=1 | | (60*10+3*10)+(60*G+3*G)= | | gx=4x^2-7 | | 8n=(4n+2)+20 | | x^-1/2-1/2x^-3/2 | | 4(d-6)+1=-11 | | 9x+3x+12= | | solve-5(2x-11)=(2x-3)-11 | | 300-16t^2=0 | | 3n-2+2(2n+1)=6n+7 | | 6+5x=2.666 | | 264=8(-5a-7) |